Motivational climate in combat sports and martial arts: Sex, body mass index and type of sport - Ortiz-Franco, Manuel; Zagalaz-Sánchez, María Luisa; Zurita-Ortega, Félix; Cachón-Zagalaz, Javier; Lindell-Postigo, David; Melguizo-Ibáñez, Eduardo (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
There is a growing interest in the motivational aspects of combat sports and martial arts practitioners due to the uniqueness of these sports modalities. The aim of this study was to establish the relationships between descriptive variables and the motivational climate of athletes practising combat sport and martial arts. This cross-sectional study was carried out on 303 athletes practising combat sports and martial arts in Spain. Motivational climate was assessed using the motivational climate questionnaires (PMCSQ-2). The results showed significant differences between motivational climate and gender, BMI, developmental stages, level of competition and for retired athletes, however, no significant differences were found for retired subjects with respect to those who continued to compete and weekly hours of practice. These results seem to suggest the convenience of using differentiated strategies, according to sex, age, level of competition or for athletes who have been retired for a period of time when working on protective factors that could increase enjoyment or performance in combat sports and martial arts.